2020
DOI: 10.1097/md.0000000000022866
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a clinical nursing pathway for percutaneous coronary intervention

Abstract: Background: Acute myocardial infarction is a very common disease in the emergency room. Emergency percutaneous coronary intervention (PCI) is the first choice to open infarct-related artery in time to regain the active blood flow of myocardial tissue. Clinical nursing pathway (CNP), namely clinical project, is an original nursing mode with good quality, outstanding efficiency, and low treatment spending, so it has attracted more and more attention. However, few studies have reported the implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This may be because the implementation of CNP enables patients to have a higher awareness of the disease and the nursing content, which mobilizes patients to better cooperate with the work of medical staff and consequently effectively improve the ability of medical staff to deal with complications and emergencies, ultimately improving the overall efficacy and prognosis of patients. Zhang et al [ 25 ] found that CNP intervention after PCI can significantly reduce hospital admission time, hospitalization expenses, LOS, and postoperative complications and improve patients' satisfaction with treatment, which was similar to our research results. According to Li and Liu [ 26 ], the implementation of CNP intervention following PCI can significantly relieve patients' bad mood and improve their QOL.…”
Section: Discussionsupporting
confidence: 91%
“…This may be because the implementation of CNP enables patients to have a higher awareness of the disease and the nursing content, which mobilizes patients to better cooperate with the work of medical staff and consequently effectively improve the ability of medical staff to deal with complications and emergencies, ultimately improving the overall efficacy and prognosis of patients. Zhang et al [ 25 ] found that CNP intervention after PCI can significantly reduce hospital admission time, hospitalization expenses, LOS, and postoperative complications and improve patients' satisfaction with treatment, which was similar to our research results. According to Li and Liu [ 26 ], the implementation of CNP intervention following PCI can significantly relieve patients' bad mood and improve their QOL.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, there are also a series of problems, such as weak pertinence, incoherent time, single mode, and inappropriate method [ 4 ]. As a standard nursing mode of clinical norms, clinical pathway nursing is a relatively mature operation system, which has been clinically used in the nursing of a variety of diseases and achieved quite significant application effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, interventional therapy for HCC is the first choice for advanced HCC treatment, and the implementation of effective clinical nursing interventions in interventional therapy can stabilize the condition of patients, reduce the occurrence of treatment complications, and promote better postoperative recovery [ 18 ]. Liao et al pointed out that CNP could improve the cognitive function and quality of life in hypertensive cerebral infarction patients [ 19 ] whereas Zhang et al clarified that CNP had an improved significance for percutaneous coronary intervention [ 20 ]. All these have laid a reliable foundation for implementing CNP in TACE for HCC.…”
Section: Discussionmentioning
confidence: 99%